2021
DOI: 10.3390/ijerph18084305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes to Architectural Elements on Human Relaxation-Arousal Responses: Based on VR and EEG

Abstract: This study combines electroencephalogram (EEG) with virtual reality (VR) technologies to measure the EEG responses of users experiencing changes to architectural elements. We analyze the ratio of alpha to beta waves (RAB) indicators to determine the pre- and poststimulation changes. In our methodology, thirty-three females experience using private rooms in a postpartum care center participated in the experiment. Their brain waves are measured while they are experiencing the VR space of a private room in a post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…Other studies have also demonstrated that a street scene that is more diverse and less fragmented leads to positive emotional experiences 16 . Furthermore, the observed variations in relaxation levels across the three groups further indicate that distinct street scales have an impact on individuals' pleasant moods, which is like previous research demonstrating that the scale of indoor spaces can elicit either good or negative physiological reactions in users 27 .…”
Section: Discussionsupporting
confidence: 78%
“…Other studies have also demonstrated that a street scene that is more diverse and less fragmented leads to positive emotional experiences 16 . Furthermore, the observed variations in relaxation levels across the three groups further indicate that distinct street scales have an impact on individuals' pleasant moods, which is like previous research demonstrating that the scale of indoor spaces can elicit either good or negative physiological reactions in users 27 .…”
Section: Discussionsupporting
confidence: 78%
“…One is the alpha waves (8-12 Hz), which appear in the state of relaxed consciousness, and the other is the beta waves (12-30 Hz), which appear in a state of active and focused thinking [19]. These EEG indicators, along with specific channels, can serve as biomarkers for analyzing relaxation and wakefulness responses in real-time, such as the RAB: α/β Ratio indicators and EEG channels F4 and F3 [20]. The Restorative Outcome Scale is a self-assessment tool for measuring emotional recovery and is extensively utilized in the field of recovery research..…”
Section: Purpose and Assumptionsmentioning
confidence: 99%
“…In 2021 Kim et al (2021) published a study on the effects of changes in architectural spaces on human responses on the relaxation-awakening plane based on VR and EEG. The study included private rooms in a postpartum care centre, presented in the form of a VR model.…”
Section: Eeg (Electroencephalography) and Vr (Virtual Reality)mentioning
confidence: 99%